A study of nondiffracting Lommel beams propagating in a medium containing spherical scatterers. (November 2016) - Belafhal, A.; Ez-zariy, L.; Hricha, Z.
Abstract: By means of the expansion of the nondiffracting beams on plane waves with help of the Whittaker integral, an exact analytical expression of the far-field form function of the scattering of the acoustic and optical nondiffracting Lommel beams propagating in a medium containing spherical particles, considered as rigid and single spheres, is investigated in this work. The form function of the scattering of the high order Bessel beam by a rigid and isolated sphere is deduced, from our finding, as a special case. The effects of the wave number-sphere radius product ( k a ), the polar angle ( φ ), the propagation half-cone angle ( β ) and the scattering angle ( θ ) on the far-field form function of the scattered wave have been analyzed and discussed numerically. The numerical results show that the illumination of a rigid sphere by Lommel beams produces asymmetrical scattering. Highlights: The scattering of the nondiffracting Lommel beams by a rigid sphere is studied. The scattered high order Bessel beam is deduced as a special case. The effects of some scattered wave parameters have been analyzed.